NETWORK-DRIVEN INTERNATIONALIZATION OF YOUNG FINNISH SPORT TECH COMPANIES TO THE US - Pyykkölä, Jasper (My University, 2018)
This study analyzes the how networks facilitate young Finnish sports technology companies internationalization to the US market. Furthermore, the purpose of this research is to contribute towards to the understanding of the role of networks in the early stages of young Finnish firms in this specific context. Despite the fact that internationalization from the network point of view has been studied extensively, the network approach in the SME level has received relatively little attention. Also, a better understanding on which firm-specific capabilities are necessary for creating crucial network ties is required. In addition to extending the knowledge base of network driven internationalization in this context, this research contributes to the established internationalization theories. The conceptual framework of this research was drawn from the network perspective to internationalization, the dynamic capabilities view and the International Entrepreneurship theory, incorporating both Born Global and International new ventures as sub-streams. It was deemed necessary to involve various streams of literature to be able to achieve the purpose of this research and answer the research question described above. The research was conducted as qualitative case study with a critical realist philosophical position. Two case companies were selected and the data was collected through semi structured, face-to-face interviews with the CEOs of both companies. The findings of this study indicate that neither of the companies would have succeeded in their internationalization to the US without the help of their networks. Establishing a position in a relevant network becomes crucial. Finding the right partners, creating and maintaining ties with important actors requires persistence and networking capability. The network base is also constantly changing reflecting the dynamism of the business environment. Both cases indicate that stronger ties are formed once the nature of the business relationships become more informal especially in the US. The findings of this research are sensitive to the specific context and thus, sets limitations to the generalizability of the results. The transferability of these results to other contexts relies solely on the reader’s discretion. Future research on the topic could broaden the scope into a variety of different industries and contextual settings to determine whether similar dynamics apply.
Keywords: International business, international entrepreneurship, internationalization, network approach, SMEs